Optimasi Tanah Napa Sebagai Adsorben ion Cu(II) - Muhamad Firdaus; Mawardi Mawardi; Amrin Amrin (Jurnal Periodic Jurusan Kimia UNP, 2013)
Has been done numerous studies to reduce levels of heavy metals in sewage waste products and many methods have been developed. Adsorption method with the right choice of adsorbent is a simple but quite effective method in removing heavy metals from wastewater. Napa soil contains high amount of silica and alumina which is 63.20% and 16.55%, the amount of silica and alumina in the soil napa almost the same with natural zeolite, so it can be used as an adsorbent. In this research, study has been conducted with the aim of determining the optimum condition of Copper(II) ion adsorption with Continuous system by napa soil adsorbent obtained from Aripan, Solok. In this research, was studied the effect of various parameters that affect the absorption capacity of the napa soil to adsorp Cu (II) ion, which is the pH of the solution, the initial concentration of the solution, the temperature of heating the adsorbent, adsorbent particle size, and the eluent flow rate. These results indicate that the optimum pH is 4, optimum initial concentration of the solution is 200 ppm, while optimum adsorbent heating temperature and optimum adsorbent particle size is 125°C  and 1700 mm respectively, and the optimum flow rate is 20 drops / min. Research data obtained was in accordance with the Langmuir adsorption isotherm curve when plotted C / m as a function of C then was obtained a linear curve which means adsorption of Cu (II) ion by Napa soil takes place chemically, adsorption affinity constant and maximum adsorption capacity was determined by using Langmuir adsorption isotherm equation which is 2.483 and 0.169 mg / g respectively.